STUDI KESALAHAN PEMAKAIAN EJAAN DAN STRUKTUR KARANGAN EKSPLANASI SISWA KELAS VIII SMP NEGERI 1 BANYUDONO - Dani Dwi Susanti; Andayani Andayani; Edy Suryanto (Universitas Sebelas Maret, 2020)
This research is a case study using descriptive qualitative methods with 21 research subjects explanatory essays written by class VIII students. The results showed that (1) there were 447 findings of spelling errors, including the writing of absorption elements (0.06%), word writing (8.27%), use of punctuation marks (18.34%), and use of letters (72, 70%) dominated by capital letters errors (70.69%) in the form of findings of patterns of capital letters errors; (2) there are seven articles that have structural errors, including the structure of the composition which is not coherent, the ambiguous type of the article, and the fact that incomplete of the structure dominates the findings of structural errors and becomes one of the triggers for other errors; (3) the factors causing the error are lack of writing practice, less thoroughness, lack of understanding of students, students' language habits, and lack of student interest in following lessons which are the dominant factors because it exacerbates other factors; (4) preventive action, students choose to learn to use spelling correctly and write explanatory text; the teacher makes direct corrections, emphasizes punishment, the use of spelling guidelines and text characteristics to students; the school, especially the principal, supervises and activates school literacy, and (5) both students, teachers and school principals provide advice to deal with these mistakes, namely the use of fun learning media and creating a comfortable learning atmosphere, habituation to using PUEBI, as well as synergy from related parties.